THE INOVATION OF DAYAH CURRICULUM IN MEETING THE NATIONAL EDUCATION STANDARDS IN ACEH - Buto, Zulfikar Ali; Hafifuddin, Hafifuddin (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2021)
Abstract: This article aims to describe the inovation of dayah curriculum and its obstacles in meeting the national education standards in Aceh. This is a qualitative study with juridical approach accredited by the National Accreditation Board of School/Madrasas (BAN-SM). The findings show that the innovation of dayah curriculum has not been implemented except for the innovation of institutional system embedded in all levels of formal education. The fulfillment of national standards for dayah education show that a very small number of dayah have met the applicable provisions, the most of them have not met several indicators of the eight standards set. Meanwhile, dayah’s obstacles in meeting national education standards include incapability of human resources, incapability of institution in managing its funds and financial reporting, the last obstacles are lack of area development, provision, and administrative management and school documentation.Keywords: inovation, dayah, Aceh, education, curriculum